2010
DOI: 10.1021/pr900736t
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectral Analysis of Neuropeptide Expression and Distribution in the Nervous System of the Lobster Homarus americanus

Abstract: The lobster Homarus americanus has long served as an important animal model for electrophysiological and behavioral studies. Using this model, we performed a comprehensive investigation of the neuropeptide expression and their localization in the nervous system, which provides useful insights for further understanding of their biological functions. Using nanoLC ESI Q-TOF MS/MS and three types of MALDI instruments, we analyzed the neuropeptide complements in a major neuroendocrine structure, pericardial organ. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 54 publications
1
76
0
Order By: Relevance
“…Our group and others have greatly expanded the peptidomes of many model organisms (3, 18 -33). For example, we have discovered more than 200 neuropeptides with several neuropeptide families consisting of as many as 20 -40 members in a simple crustacean model system (5,6,(25)(26)(27)(28)(29)(30)(31)34). However, a majority of these neuropeptides are small peptides with 5-15 amino acid residues long, leaving a gap of identifying larger signaling peptides from organisms without sequenced genome.…”
mentioning
confidence: 99%
“…Our group and others have greatly expanded the peptidomes of many model organisms (3, 18 -33). For example, we have discovered more than 200 neuropeptides with several neuropeptide families consisting of as many as 20 -40 members in a simple crustacean model system (5,6,(25)(26)(27)(28)(29)(30)(31)34). However, a majority of these neuropeptides are small peptides with 5-15 amino acid residues long, leaving a gap of identifying larger signaling peptides from organisms without sequenced genome.…”
mentioning
confidence: 99%
“…They can also be detected in many other organs of the American lobster. 48 These three families display similar patterns in Figure 6, and the representative trend of orcokinin at m / z 1502.69 is shown in green trace in Figure 7. Previous reports indicated that FMRFamide and orcokinins appeared in the STNS as early as midembryonic stage (E50).…”
Section: Resultsmentioning
confidence: 63%
“…Notably, the neuropeptides are not evenly distributed in the brain. 47,48 The conversion here is just an approximation to facilitate neurobiologists’ understanding of relationship of total neuropeptide abundance as a function of lobster developmental stage. The calculated results for four selected peptides are illustrated in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, two Atype allatostatins PRNYAFGLamide (m/z 936.51) and PRDYAFGLamide (m/z 937.49) were recently sequenced from the pericardial organs of H. americanus by nanoLC ESI QTOF MS/MS. 37 To test whether they exist in the STG, CE separation was employed to resolve these peaks. Figure 3a is a zoom-in spectrum of the STG extract, showing CabTRP Ia and its isotope envelope.…”
Section: ■ Results and Discussionmentioning
confidence: 99%